Dynamic regulation and functions of mRNA m6A modification - Wang, Shanshan; Lv, Wei; Li, Tao; Zhang, Shubing; Wang, Huihui; Li, Xuemei; Wang, Lianzi; Ma, Dongyue; Zang, Yan; Shen, Jilong; Xu, Yuanhong; Wei, Wei (Cancer cell international, 2022)
N 6 -Methyladenosine (m6A), the most abundant internal modification associated with eukaryotic mRNAs, has emerged as a dynamic regulatory mechanism controlling the expression of genes involved in many physiological activities by affecting various steps of mRNA metabolism, including splicing, export, translation, and stability. Here, we review the general role of m6A, highlighting recent advances related to the three major types enzymes that determine the level of m6A modification (i.e., writers, erasers, and readers) and the regulatory mechanism by which m6A influences multiple stages of RNA metabolism. This review clarifies the close connection and interaction between m6A modification and nuclear gene expression, and provides key background information for further studies of its roles in numerous physiological and pathophysiological processes. Among them, perhaps the most eye-catching process is tumorigenesis. Clarifying the molecular mechanism of tumorigenesis, development and metastasis in various tissues of the human body is conducive to curbing out-of-control cell activities from the root and providing a new strategy for human beings to defeat tumors.